Current status of the California sea lion (Zalophus californianus) and the northern elephant seal (Mirounga angustirostris) at the San Benito Archipelago, Mexico - Fernando R Elorriaga-Verplancken; Giulia Ferretto; Olivia C Angell (Ciencias Marinas, 2015)
The California sea lion (CSL) and the northern elephant seal (NES) are the two most abundant pinniped species inhabiting the San Benito Archipelago (Baja California, Mexico). This study reports the results of the first survey to gather abundance information from continuous breeding seasons (2012–2015) and over the course of a single year (2014). Relative to the previous year, the abundance of CSLs declined in July 2014; however, based on historical censuses, the colony at the archipelago was catalogued as “stable”. Intra-annually, the CSL abundance was regulated by pups and adult females, which reached their peak during the breeding season (July). Moreover, we hypothesize that subadult males from the west coast of Baja California enter the Gulf of California. The NES fluctuations were most affected by the breeding season (February), when the number of pups and adult females peaked, and by the important presence of juveniles in May and September. The NES colony at the archipelago was catalogued as “in decline”, based on previous countings. This high-resolution survey complements past and future studies in the region, and adds another dimension to our understanding of these species, which is largely based on information from their main rookeries in California.